THE IMPACT OF HUMAN CAPITAL ON THE ECONOMIC DEVELOPMENT OF THE COUNTRY - Sherkhanov Iftikhor Abdulrazzoqovich (Journals Park Publishing, 2025)
The article explores how human capital influences a country's economic growth. It highlights that investing in human capital, with a focus on education and healthcare, along with government-led reforms, serves as an effective means to boost population income. The research also examines regional variations in per capita income. In conclusion, the article discusses how the development of human capital affects key macroeconomic indicators such as income levels, unemployment, and inflation, and offers proposals and recommendations for further enhancing human capital.
Keywords: Human capital, population income, education, healthcare, standard of living, social sphere.